The Effect of a Denture Adhesive on the Colonization of Candida Species In Vivo - Eunghwan Kim, DDS, MS,1 Carl F. Driscoll, DMD,2 and (Journal of Prosthodontics, 2003)
The purpose of this study was to evaluate the effect of a single denture adhesive on oral quantities of Candida species in vivo by determination of absolute and proportional counts of Candida species on dentures and in saliva of individuals who used this denture adhesive for a period of 14 days